Germany's 1875 Banking Act and the genesis of a monetary framework: 1866-76 - Hendrik Klaus (IBF - Institut für Bank- und Finanzgeschichte e.V., 2025)
– This paper explores the genesis of the German monetary framework between 1866 and 1876, with a specific focus on the 1875 Banking Act. The Banking Act constituted the final piece within the legislation that established Germany's post- unification monetary order, regulated bank note issuance across the Reich, and established the Reichsbank as Germany's first central bank. The Banking Act has rarely featured prominently in the literature, and it has often been regarded as a subordinate aspect of Germany's adoption of a gold currency. Drawing on a broad range of primary sources, this study argues that the Banking Act was in fact the most complicated and politicised element of the monetary reform. The debates on the centralisation of note issuance and banking functions are a fascinating window into how late nineteenth-century monetary management developed within the political imperatives of the time. As a case study, the historical perspective on the development of Germany's monetary framework is relevant in a broader context. It offers insight into the dynamics that have shaped political economies past and present, and it enables us to reflect critically on outcomes and alternatives for specific forms of monetary governance
Keywords: N13; N23; B15; B17; 330; Bankgesetz; Banking Act; Reichsbank; Ludwig Bamberger; Otto Michaelis; financial history; central bank history; free banking